HUMAN RESOURCES MANAGEMENT IN PUBLIC ADMINISTRATION – LIMITS - CENUSER-PANCZEL ANDREEA; MUSCALU EMANOIL (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2015)
Due to its size, and to the number of activities it encompasses, the public sector has an essential place in the continued working of the state system. This article treats the aspects and particularities of human in Romanian public administration, as well as the obstacles that come from the internal or external medium the management of that level faces. The duties that the public administration must deal with are diverse and need to have the management of human resources oriented towards action, the individual and the future.